The Role of Teachers in Simple Sentence Writing Learning for Primary School Students - Windah Gema Sari; Febrina Dafit (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to determine the role of teachers in the development of primary school pupils' ability to compose basic phrases. The descriptive qualitative research approach was adopted in this study. The information was gathered through observation, interviews, and the review of records. Participants in the study were first-grade instructors at SDN 151 Pekanbaru, in the province of Riau. Data triangulation is used in the data credibility test because it allows researchers to double-check their findings by comparing them to other sources. According to the Miles and Huberman data analysis model, there are three steps: (1) data collection (data collection), (2) data presentation (data presentation), and (3) conclusion formulation and verification (conclusion drawing). The findings of the study indicate that the teacher's role in helping grade I students at SDN 151 Pekanbaru learn to write basic sentences has been going fairly well, with numerous stages, such as being a teacher, mentor, trainer, and learning manager, all of which have been quite successful. In addition to improving the quality of the teaching and learning process by providing adequate learning facilities, the findings of this study have broader ramifications.